Biofilm and Dental Biomaterials - Øilo, Marit (Materials (Basel), 2015)
All treatment involving the use of biomaterials in the body can affect the host in positive or negative ways. The microbiological environment in the oral cavity is affected by the composition and shape of the biomaterials used for oral restorations. This may impair the patients’ oral health and sometimes their general health as well. Many factors determine the composition of the microbiota and the formation of biofilm in relation to biomaterials such as, surface roughness, surface energy and chemical composition, This paper aims to give an overview of the scientific literature regarding the association between the chemical, mechanical and physical properties of dental biomaterials and oral biofilm formation, with emphasis on current research and future perspectives.